2008
DOI: 10.2166/wst.2008.292
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and uncertainty of wastewater turbidity measurements

Abstract: Turbidity monitoring is a valuable tool for operating sewer systems, but it is often considered as a somewhat tricky parameter for assessing water quality, because measured values depend on the model of sensor, and even on the operator. This paper details the main components of the uncertainty in turbidity measurements with a special focus on reproducibility, and provides guidelines for improving the reproducibility of measurements in wastewater relying on proper calibration procedures. Calibration appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…The dry weather ratios are less variable and display lower overall values than their wet weather counterparts; this result can be explained by the type of particles involved Water Science a Technology | 64. during wet weather (i.e. less homogeneous, more mineral in nature, finer-grained, see Joannis et al (2008)). …”
Section: Analysis Of the Variability In Ratio A¡¡ Between Tss And Turmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry weather ratios are less variable and display lower overall values than their wet weather counterparts; this result can be explained by the type of particles involved Water Science a Technology | 64. during wet weather (i.e. less homogeneous, more mineral in nature, finer-grained, see Joannis et al (2008)). …”
Section: Analysis Of the Variability In Ratio A¡¡ Between Tss And Turmentioning
confidence: 99%
“…Recent studies have demonstrated how it can be used to control and evaluate effiuent quality (Langeveld et al 2005;Lawler et al 2006), but it must be emphasized that the use of suitable methods is mandatory to obtain reliable and accurate continuous turbidity measurements within the sewer system over short time steps (Joannis et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity data were recorded every minute during one year, according to a protocol that has led to reliable and accurate measurements (Joannis et al 2007). Table 1 lists the main characteristics of the two catchments associated with these measurement points.…”
Section: Field Datamentioning
confidence: 99%
“…The development potential of quality-based RTC strategies bowever is constrained by a lack of available quality data in sewer systems. Recent studies bave doi: lü,2166/wst,20U,545 demonstrated the use of continuous turbidity measurements in monitoring and assessing sewer system effluent quality (Langeveld et al 2005;Joannis et al 2007). Turbidity is well correlated witb suspended solids (SS) in sewer systems (Ruban et al 2001;Mels et al 2004;Fletcber & Delefic 2007;Lacour et al 2009), and SS are recognised as tbe primary source of pollution transfer witbin sewer systems (Chebbo et al 1995;Ashley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the potential for using turbidity sensors to continuously monitor pollutant discharges (Langeveld et al 2005;Lawler 2005;Joannis et al 2007). When strict protocols are applied, turbidity sensors are able to provide accurate and reproducible data, both in the laboratory and in situ (Joannis et al 2007).…”
Section: Introductionmentioning
confidence: 99%